Café-au-lait spots and pulmonary stenosis: Watson syndrome due to fresh mutation. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
Case report. An 8-month-old boy was first observed due to the presence of atopic dermatitis and café-au-lait spots. The family history was positive for atopy and negative for neurofibromatosis, Noonan syndrome and Watson syndrome. Physical examination showed symmetric vesicles and papules of the cheeks (Fig. 2) and a score of café-au-lait spots distributed on the entire skin surface. The largest spot, sized 8 cm x 3 was present on the left hemithorax (Fig. 1); axillary lentiginosis was not present (Fig. 2). The search for Lisch nodules was negative in the child and his parents. The echocardiography (Fig. 3) showed subvalvular stenosis of the main trunk of the pulmonary artery with peak gradient of 45 mmHg. The cutaneous and cardiac findings led to the final diagnosis of Watson syndrome likely due to fresh mutation.